THE USE OF POKUS (POLITICS OF KHULAFAUR RASYIDIN) FLIPBOOK IN INCREASING ELEMENTARY STUDENTS' LITERACY INTEREST - Viriya Lishetiyana; Santi Septiani; Dwi Imelda Talia; Ani Nur Aeni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper is based on the existence of an issue caused by the development of technology, which has a considerable effect on the field of education. The issue influences the learning media used to be changed as well as low students' interest in literacy. Interest in literacy is essential in realizing the learning process for students, especially elementary students. Hence, the researchers created a learning medium in the form of a digital-based book entitled POKUS (Politic of Khulafaur Rasyidin) Flipbook as one of the digital-based media that can be used in the 21st century. The research uses the Design and Development (D&D) method in the form of ADDIE development. The POKUS flipbook, which contains material regarding the Khulafaur Rasyidin and is packaged in an attractive design and is easily understood by elementary students. The POKUS flipbook had been tested for the effectiveness of its use by teachers as well as students and indicated results of 95.7% and 85.5%. It implies that the POKUS Flipbook is feasible to use. In addition, 91.1% of POKUS Flipbooks were able to increase elementary students' literacy interest.